The Impact of Entrepreneurial Competency on the Empowerment of Community Learning Centre Managers - Ambarini, Erna; Sasmita, Karta; Irvansyah, Adi (Journal of Nonformal Education, 2025)
Background -. Educational disparities, dropout rates, and limited PKBM (Community Learning Center) management capacity remain key challenges. This study takes Bekasi Regency—an urban–semi-urban area with strong entrepreneurial commitment—as its research locus.Research Urgency - Strengthening the managerial and entrepreneurial capacity of PKBM leaders is crucial to sustaining Indonesia’s non-formal education ecosystem. Despite the government’s focus on lifelong learning and community empowerment, many PKBMs struggle to operate independently due to weak institutional management, limited innovation, and low digital adaptation. Addressing this issue is urgent to ensure that community-based education remains relevant, financially viable, and aligned with the goals of inclusive human development in the digital era.Research Objective - This study aims to analyze the effect of entrepreneurial competencies on the empowerment of PKBM managers in Bekasi Regency, and to identify generational patterns in management practices. The research further seeks to propose a competency-based empowerment model that integrates entrepreneurial skills, innovation, and digital networking to enhance the sustainability of community learning centers.Research Methods - This study uses a sequential explanatory mixed-methods design to examine the relationship between entrepreneurial competencies and PKBM managers’ empowerment in Bekasi Regency. Quantitative data from 50 purposively sampled managers were analyzed using CFA and PLS-SEM, while qualitative interviews provided contextual insights, validated through triangulationResearch Findings - Entrepreneurial competencies show a strong positive association with PKBM managers’ empowerment (path coefficient = 0.971, p < 0.001), accounting for 94.2% of the variance explained by the model. The analysis also indicates a generational divide: senior managers (>7 years’ experience) tend to rely on trial-and-error approaches (78%), whereas junior managers (